Penggunaan Fly Ash sebagai Material Bata Beton untuk Meningkatkan Daya Peredaman Panas pada Ruangan - Napitupulu, Robert; Chardova, Andreas; Kurniawan, Zaldy (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
The use of fly ash as an additive for concrete bricks has a positive impact on the environment, in addition to reducing environmental pollution. Fly ash has a silicate content that is similar to cement, the addition of fly ash to the concrete brick mixture can be a good mineral additive for concrete bricks because fly ash contains silica which is binding. This study aims to determine the effect of fly ash waste as an additive on heat reduction and to determine the highest and lowest composition values ??for the addition of fly ash waste to concrete bricks in order to reduce heat. The method used in this study is the full factorial method with process variables of fly ash: sand 10%: 60%, 20%: 50%, 30%: 40% and drying time of 3 and 5 days, and a heat reduction test was carried out as a response observed with a total of 6 specimens and 3 replications for each specimen. Based on the research results obtained, it shows that specimens with fly ash: sand 30%: 40% with a drying time of 5 days get the highest value of 6.6oC. while fly ash: 10% sand: 60% with a drying time of 3 days obtained the lowest value of 4oC.